Pengaruh Modal Kerja, Aktivitas, Inflasi terhadap Pertumbuhan dan Laba dengan Moderasi Kebijakan Dividen Bank Buku IV - Irfan Musadat; Agung Pramayuda; Retno Widya Ningrum (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of Working Capital, Company Activity, and Inflation Rate on Company Growth and its impact on Profit Achievement, with Dividend Policy as a moderating variable. The object of this research focuses on banking companies categorized as BUKU IV Banks in Indonesia during the period 2018–2025. This study employs a quantitative approach using panel data analysis methods. The data used are secondary data obtained from companies’ annual financial reports and publications from Bank Indonesia. The analytical techniques include panel data regression, direct effect testing, mediation testing through company growth variables, and moderation testing to examine the role of dividend policy and tax policy in strengthening or weakening the relationship between company growth and profit achievement. The data are processed using EViews 9 software. Theoretically, this research contributes to the development of financial literature by integrating internal and external financial aspects into a single analytical framework, as well as positioning dividend policy and tax policy as moderating mechanisms in the relationship between company growth and profitability. Practically, the results of this study are expected to serve as a reference for banking management, regulators, and investors in formulating financial policies that support sustainable growth and improved profit achievement.